Faktor-Faktor Yang Berhubungan Dengan Praktik Wanita Pekerja Seks (WPS) Jalanan Dalam Upaya Pencegahan IMS Dan HIV/AIDS Di Sekitar Alun-Alun Dan Candi Prambanan Kabupaten Klaten - Budiman, Nurcholis Arif; Istiarti, Tinuk; BM, Syamsulhuda (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2008)
Background: Data from Serro Survey about STI and HIV & AIDS in Klaten in 2005 showed, 5 FSWs (8.4%) have syphilis infected from 59 FSWs followed testing and in 2006, 8 FSWs (18%) have syphilis infected and 1 (2.2%) FSW has HIV infection.Method: The aim of this study was to know factors related practicing Street FSWs for protecting STI and HIV & AIDS around Klaten Square and Prambanan Temple, Klaten. This research was an observational study using cross sectional approach. Questionnaire used for data collecting with 44 samples. Data analyses of this study were univariate, bivariate by chi square and multivariate by logistic regression.Result: The result of this research showed there were relation between knowledge about STI and HIV & AIDS (p value = 0.032), perceived susceptibility on infecting STI and HIV & AIDS (p value = 0.001). Some variables not related in this research, there were age, education, marital status, income, working period, perceived severity, perceived benefit, perceived barrier, and cues to action. This research don’t have dominant dependent variable related practicing Street FSWs on protecting STI and HIV & AIDS, but perceived severity was a variable resemble significant (p-value=0.092). Klaten Health Office especially Communicable Disease Control Program suggest to make an advocacy for STI and HIV & AIDS. Increase knowledge about STI and HIV & AIDS and perceived susceptibility, severity, benefits and cost through promotion by Health Officer.Keywords: street female sex workers (FSWs), practicing for protecting STI, HIV and AIDS